Exploring the Implementation of Talk Hunt Media in Enhancing Students' Interest in Learning English - Wahyuni, Nadia Nur; Zainuddin, Zainuddin; Ferdiyanto, Feri (Journal of English Language and Education, 2026)
English learning requires instructional strategies that can actively engage students and increase their interest in the learning process. However, many English classrooms are still dominated by teacher-centered instruction that limits students’ participation and reduces their motivation to learn. This study aims to explore the implementation of Talk Hunt media in enhancing students’ interest in learning English. The study employed a descriptive qualitative research design and was conducted with 16 tenth-grade students at Darul Lughah Wal Karomah Senior High School. Data were collected through classroom observation, semi-structured interviews, and documentation. The findings reveal that the implementation of Talk Hunt media created a more interactive and student-centered learning environment. Students demonstrated higher enthusiasm, participation, confidence, and engagement during the learning process. The study concludes that Talk Hunt media is an effective and practical instructional media to enhance students’ interest and create a more communicative English learning atmosphere.